Psychological barriers in the cryptocurrency market - Fonseca, Vítor (2019)
Purpose: The purpose of this paper is to study the existence of psychological barriers in cryptocurrencies. Design/methodology: To detect psychological barriers we perform a uniformity test, a barrier hump test, a barrier proximity test and conditional effects test to a sample comprised by the daily closing quotes of six of the most liquid cryptocurrencies. Findings: The results evidence the existence of psychological barriers in four of the cryptocurrencies under scrutiny, namely, Bitcoin, Dash, NEM and Ripple. Practical implications: The fact that the cryptocurrency market has a high share of unexperienced investors and presents several cases of psychological barriers is consistent with the hypothesis that that class of investors is particularly prone to the behavioral biases which cause psychological barriers. Originality/value: This paper studies for the first time the existence of psychological barriers in the market of cryptocurrencies.